2017
DOI: 10.1021/acsnano.7b06664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grafting Density on Block Polymer Self-Assembly: From Linear to Bottlebrush

Abstract: Grafting density is an important structural parameter that exerts significant influences over the physical properties of architecturally complex polymers. In this report, the physical consequences of varying the grafting density (z) were studied in the context of block polymer self-assembly. Well-defined block polymers spanning the linear, comb, and bottlebrush regimes (0 ≤ z ≤ 1) were prepared via grafting-through ring-opening-metathesis polymerization. ω-Norbornenyl poly­(d,l-lactide) and polystyrene macromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 67 publications
3
122
1
2
Order By: Relevance
“…Figure S13 shows a sketch of the proposed backbone kinking that results in a more "flexible" chain, which is similar to the torsional limitations that Lin et al observed. 13 Figure S13. Cartoon depiction of backbone folding back on itself to space out side chains.…”
Section: Change In Conformation With Grafting Densitymentioning
confidence: 99%
“…Figure S13 shows a sketch of the proposed backbone kinking that results in a more "flexible" chain, which is similar to the torsional limitations that Lin et al observed. 13 Figure S13. Cartoon depiction of backbone folding back on itself to space out side chains.…”
Section: Change In Conformation With Grafting Densitymentioning
confidence: 99%
“…Lattice spacings on the order of d 0 = 100 nm are consistently reported in the literature . Several intricate designs of BBCPs are reported with variable graft density, block composition, and side chain chemistries . BBCPs have found practical use as templates for the fabrication of functional materials such as coatings, photonic crystals, scaffolds for well‐ordered nanoparticle arrays, metallo‐dielectric composites, and novel elastomeric materials …”
Section: Introductionmentioning
confidence: 86%
“…Interestingly,the domain spacing was noted to be insensitive to the backbone length, which suggested the brushes were undergoing phase separation of their side chains,with the backbone confined at the interface between the two polymers and the side chains segregated to opposite sides (i.e.a long the x axis). [52] Increases in the degree of polymerisation of the brush backbone led to increasing domain spacing in the respective thin films,w ith ar emarkable near-linear relationship observed. These lamellar domains had dimensions which depended on the backbone length and were large enough to reflect visible light.…”
Section: In Thin and Bulk Filmsmentioning
confidence: 96%
“…[52] Increases in the degree of polymerisation of the brush backbone led to increasing domain spacing in the respective thin films,w ith ar emarkable near-linear relationship observed. [52] with permission.C opyright 2017 AmericanC hemical Society.E )The reflectance of the bulk self-assembled thin films is related to the molecularw eight of the compartmentalised brushes. [20a] Thedomain spacing may also be adjusted by altering the self-assembly conditions,s uch as changing the annealing solvent and temperature, [20a] as well as by the blending in of additives (e.g.…”
Section: In Thin and Bulk Filmsmentioning
confidence: 96%